Female Education and Per Capita Income of Households: Evidence from Three Dimensional Surface Maps of a Small Village - Gul, Ejaz (International Journal of Economics and Financial Issues, 2017)
Woman has been the crucial socio-economic sufferer especially those living in the rural areas of developing countries. It has been established through extensive research that women represent the major percentage of poor on the global landscape. Why it is so? The answer is not very difficult. Gender biases, gender exploitation, low income, deprivation, violation of basic rights are all social ailments that female has to face in society. In this scenario, female education has significant role. With female education, poverty reduces and socio-economic status of the households improves. This paper investigates the critical linkage between female education and per capita income of households in a small village of Khyber Pakhtunkhwa Province of Pakistan. Computer Assisted Qualitative Data Analysis Software (CAQDAS) was used to develop three dimensional digital models of the female education and per capita income of the households. Based on the these models, three dimensional surface maps were prepared for female education and per capita income for the whole village which revealed that parts of village with higher female education had higher per capita income compared to parts of village with low female education. Paper clearly addresses the significance of female education to improve socio-economic fabric of the rural society of Pakistan. Keywords: Female, education, poverty, per capita, income, maps. JEL Classifications: D04, D31, I121, I124